Determination of elements in sandstone using laser-induced breakdown spectroscopy assisted by the laser fusion method. Issue 9 (3rd August 2022) - Zheng, Ruiqin; Wu, Mengfan; Zeng, Lingwei; Rao, Yu; Chen, Sha; He, Xingliang; Pei, Hongliang; Wang, Xu; Duan, Yixiang
Abstract : Glass beads with improved physical properties were obtained by high-frequency pulse laser fusion of sandstone samples, which improved the stability of the LIBS signal. Abstract : Laser-induced breakdown spectroscopy (LIBS) is prevalent in the direct qualitative and quantitative analysis of rock samples. However, for sandstone samples with high SiO2 content (about 90%), it is difficult to prepare samples and they perform poorly in quantitative analysis. Here, a laser fusion pre-treatment method of sandstone samples for quantitative analysis in LIBS is proposed. The laser fusion method uses a quasi-continuous pulse laser with a high frequency (50 kHz) to interact with the sandstone powder sample in a short time (20 seconds), making the sandstone powder sample through a heating, fusing, cooling, and solidification process, to obtain glass beads of a more stable physical matrix. The results of LIBS spectral data obtained by the laser fusion method and traditional pellet method were compared. For certified reference materials (CRMs), the linearity of calibration curves of elements (Al, Ba, Ca, Fe, Mg, Sr, K, and Na) by the laser fusion method ( R 2 = 0.903–0.980) is better than that of the pellet method ( R 2 = 0.275–0.863). Not only were the detection limits of laser fused samples (0.7–104.7 ppm) lower than those of pellet samples (4.5–377.6 ppm), but the relative standard deviations (RSD) of spectral signal intensity of the laser fused samples ranged from 1% to 10%, which was about one-third of that of pellet samples on average. Therefore, the glass beads with high uniformity, flatness, and hardness obtained by the laser fusion method are conducive to signal detection of LIBS technology, which can effectively improve the stability of the signal and the precision of detection results.